Advances in the Astonishing World of Phytochemicals: State-of-the-Art for Antioxidants - D'Anneo, Antonella; Lauricella, Marianna (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint represents a collection of scientific papers belonging to a Special Issue of Antioxidants entitled "Advances in the Astonishing World of Phytochemicals: State-of-the-Art for Antioxidants". Several studies have revealed that plants are a source of a plethora of bioactive compounds, such as phytohormones, glycosides, terpenoids, alkaloids, phenolic compounds, and essential oils, with a strong potential impact in the fields of pharmaceutics and agriculture. These phytochemicals represent a valuable weapon that plants use in self-defense in order to counteract the effects of abiotic stress disturbing the delicate equilibrium between the generation of reactive oxygen species (ROS) and antioxidant defense systems. In recent years, interest in this area of research has been increasing due to the multifaceted properties of natural compounds with antioxidants having anticancer, anti-inflammatory, and antimicrobial activity. Therefore, understanding the underlying mechanism of their action is crucial to establishing their real potential in applied sciences. This reprint focuses on the most recent advances in the study of antioxidant molecular mechanisms activated by phytochemicals, with potential pharmacological and agricultural applications. We thank all the authors for their contribution to the research topic of this reprint and all editorial staff for their valuable support.